The Promise of Systems Biology in Clinical Applications - Yip, Y. L.; Managing Editor for the IMIA Yearbook Section on Bioinformatics (Yearbook of Medical Informatics, 2008)
Objectives To summarize current excellent research in the field of bioinformatics.Method Synopsis of the articles selected for the IMIA Yearbook 2008.Results Current research in the field of Bioinformatics shows that the emergent field of systems biology is starting to offer innovative solutions to clinically-relevant problems. The approach used can be top-down, where models are created based on hypotheses to describe previously unexplained phenomena and then tested against experimental or clinical evidence. It can also be bottom-up, where mathematical models are built by harnessing existing information about the components (e.g. protein entities, interaction networks) of a system in order to discern critical system-level mechanisms that can be relevant for clinical applications. Progress in this area is aided by the ongoing development in data integration and management, whose current focus is on better semantics for facilitating translational research. Advances in other important areas, such as microarray technology, text mining and ontologies, are also noted.Conclusions The best paper selection of articles on bioinformatics gives examples of original research that exploits mathematical modeling to tackle medical problems and of improved semantic solutions for data integration. As new directions are explored and the technologies mature, these approaches are expected to be increasingly integrated into clinical practice.
Keywords: International Medical Informatics Association; IMIA Yearbook; bioinformatics; systems biology